1972
DOI: 10.1085/jgp.59.3.347
|View full text |Cite
|
Sign up to set email alerts
|

The Capacitance of Skeletal Muscle Fibers in Solutions of Low Ionic Strength

Abstract: The capacitance of skeletal muscle fibers was measured by recording with one microelectrode the voltage produced by a rectangular pulse of current applied with another microelectrode. The ionic strength of the bathing solution was varied by isosmotic replacement of NaCl with sucrose, the [K] [C1] product being held constant. The capacitance decreased with decreasing ionic strength, reaching a value of some 2 F/cm 2 in solutions of 30 mM ionic strength, and not decreasing further in solutions of 15 mM ionic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
3
18
0
Order By: Relevance
“…3 practically no twitch tension could be detected at external Na+ concentrations below 40 mm, at least for the experimental conditions used here. This result is at variance with those of Overton (1902), Edwards, Ritchie & Wilkie (1956), Mashima & Matsumura (1962), Grabowski, Lobsiger & Littgau (1972), and Vaughan, Howell & Eisenberg (1972), whose experiments indicate that at [Na+]. = 40 ml the twitch tension is still practically normal.…”
Section: Methodssupporting
confidence: 66%
“…3 practically no twitch tension could be detected at external Na+ concentrations below 40 mm, at least for the experimental conditions used here. This result is at variance with those of Overton (1902), Edwards, Ritchie & Wilkie (1956), Mashima & Matsumura (1962), Grabowski, Lobsiger & Littgau (1972), and Vaughan, Howell & Eisenberg (1972), whose experiments indicate that at [Na+]. = 40 ml the twitch tension is still practically normal.…”
Section: Methodssupporting
confidence: 66%
“…As mentioned above, Tamasige (1950) found a membrane resistance of 10,000 2. cm2. Vaughan, Howell & Eisenberg (1972) …”
Section: Discussionmentioning
confidence: 99%
“…Vaughan et al (1972) have reported large drops in Cm when ionic strength of Ringer fluid is lowered by replacing NaCl isosmotically with sucrose. Their work was carried out with a constantcurrent technique, and it seemed ofinterest to repeat some oftheir measurements with the present method.…”
Section: Inaccurate Determination Offibre Lengthmentioning
confidence: 99%
“…Membrane constants of eight fibres were also measured in a lowconductivity Ringer fluid (solution K in Table 1) identical in composition to '0-24 IS Ringer' of Vaughan et al (1972). Mean values + S.E.…”
Section: Inaccurate Determination Offibre Lengthmentioning
confidence: 99%
See 1 more Smart Citation